Improved Treatment of Pancreatic Cancer With Drug Delivery Nanoparticles Loaded With a Novel AKT/PDK1 Inhibitor. Issue 8 (September 2016) - Kobes, Joseph E.; Daryaei, Iman; Howison, Christine M.; Bontrager, Jordan G.; Sirianni, Rachael W.; Meuillet, Emmanuelle J.; Pagel, Mark D.
Abstract : Objectives: This research study sought to improve the treatment of pancreatic cancer by improving the drug delivery of a promising AKT/PDK1 inhibitor, PHT-427, in poly(lactic-co-glycolic) acid (PLGA) nanoparticles. Methods: PHT-427 was encapsulated in single-emulsion and double-emulsion PLGA nanoparticles (SE-PLGA-427 and DE-PLGA-427). The drug release rate was evaluated to assess the effect of the second PLGA layer of DE-PLGA-427. Ex vivo cryo-imaging and drug extraction from ex vivo organs was used to assess the whole-body biodistribution in an orthotopic model of MIA PaCa-2 pancreatic cancer. Anatomical magnetic resonance imaging (MRI) was used to noninvasively assess the effects of 4 weeks of nanoparticle drug treatment on tumor size, and diffusion-weighted MRI longitudinally assessed changes in tumor cellularity. Results: DE-PLGA-427 showed delayed drug release and longer drug retention in the pancreas relative to SE-PLGA-427. Diffusion-weighted MRI indicated a consistent decrease in cellularity during drug treatment with both types of drug-loaded nanoparticles. Both SE- and DE-PLGA-427 showed a 6-fold and 4-fold reduction in tumor volume relative to untreated tumors and an elimination of primary pancreatic tumor in 68% of the mice. Conclusions: These results indicated that the PLGA nanoparticles improved drug delivery of PHT-427 to pancreatic tumors, which improved the treatment of MIA PaCa-2 pancreatic cancer.